THE INCIDENCE OF UNDUE COMPARISON IN THE TELECOMMUNICATIONS SECTOR CASE STUDY - Lazo Paiva, Rossmery (2025)
The Peruvian market is highly competitive, and advertising plays an important role in economic development, by promoting the offer of services and/or products. However, there is no clear prior legislative or jurisprudential criterion for its regulation, which can lead to acts of unfair competition. The objective of this work is to establish the incidence of improper comparison in the telecommunications sector in Peru, through a qualitative approach methodology, of a basic type, with a descriptive level, an inductive method, and with a study design of case, using the documentary analysis technique. The results demonstrated the incidence of improper comparison in unfair competition within the telecommunications sector, given that this type of act can cause potential or real damage to the competitor, through a decrease in subscribers. It should be noted that concurrent damage is permitted, as long as the requirementsof exceptio veritatis (accuracy, objectivity and relevance) are met. Finally, in the present case, the existence of the unequivocal indirect allusion was established, through the structure of the market and the additional elements, which constitutes an improper comparison for damaging the image, without complying with the requirements established in the Legislative Decree 1044.